The PENGENALAN PEMANFAATAN GOOGLE SITES UNTUK PEMBUATAN WEB DI MI HIDAYATULL ATHFAL GUNUNG SINDUR: PENGENALAN PEMANFAATAN GOOGLE SITES UNTUK PEMBUATAN WEB DI MI HIDAYATULL ATHFAL GUNUNG SINDUR - Diki Rasapta; Septa; Syndhe Qumaruw Syty; Abdal Jabar (Abdi Jurnal Publikasi, 2022)
In the era of globalization where technology, information and communication (ICT) is developing very rapidly, the world of education has experienced changes in its management as a result of the demands of using technology. The implementation of learning is not only based on offline/off-the-network basis, but with the support of learning technology it can be done online/in the internet network. Changes in learning and demands for innovation are important things to do (Amin, 2017). Computers as learning media have advantages in graphic presentations with an attractive appearance, which can be freely manipulated in the form of visual representations. One type of media that is appropriate in the learning process is the Google Site Application. In this PKM, we share a little knowledge about how to create a simple website using Google Sites. Because in the current era, technological developments are developing rapidly, what's more with the internet we can create websites for various needs such as selling online, creating learning media, creating personal articles and introducing a person's or company's profile. Website is an application that is very fast growing and most widely used. From the information system that is in great demand from an agency or institution is a website which is a facility that displays and searches for information. And the benefit of using Google Sites is to add insight into the use of Google Sites intelligently. The purpose of this training is to introduce the world of the internet, especially the creation and use of websites. Therefore, we students feel we have to introduce the current developments in internet technology, especially regarding websites. We hope that the training that has been carried out can increase the knowledge of the students in terms of using the website for everyday life. One of the products of information and communication technology is a website. Websites are used by many activities related to communication and information that can present information quickly and precisely. Currently, there are many information facilities and means available to make it easier to get information. This website learning aims to provide knowledge to students about the uses and benefits that can be obtained by learning websites. Keywords: Website, GoogleSite, Internet, Computer, Information